Validation of Pediatric Weight Estimation Formulae in a Suburban Cameroonian Population: A Cross-sectional Study. (12th April 2018) - Mbanga, Clarence Mvalo; Agbor, Valirie Ndip; Ditah, Chobufo; Toukam, Louise Daniele; Njim, Tsi
Abstract: We assessed the accuracy of the Nelson, Best Guess and Advanced Pediatric Life Support (APLS) formulae in estimating weight in a suburban Cameroonian pediatric population, by conducting a cross-sectional study using 544 children aged 1 month to 12 years. Agreement between measured and estimated weight was poor for Nelson [concordance correlation coefficient (CCC) 0.89 (95% confidence interval (CI) 0.87–0.90)] and Best Guess [CCC 0.88 (95% CI 0.86–0.90)] formulae, and moderate for the APLS formula [CCC 0.92 (95% CI 0.90–0.93)]. On Bland–Altman analysis, all three methods had limits of agreement (APLS −42.2 to –45.6%, Best Guess −42.7 to –55.1%, Nelson −36.4 to –42.4%) above the −10 to –10% set as criteria for clinical agreement. Conclusively, the accuracy of all three formulae was clinically unacceptable in our study population, suggesting the need for studies aimed at deriving more accurate formulae adapted for use in our context.